Challenges adopting next-generation sequencing in community oncology practice. Issue 5 (September 2021) - Ashbury, Fredrick D.; Thompson, Keith; Williams, Casey; Williams, Kirstin
Abstract : Purpose of review: We are in an exhilarating time in which innovations exist to help reduce the impact of cancer for individuals, practitioners and society. Innovative tools in cancer genomics can optimize decision-making concerning appropriate drugs (alone or in combination) to cure or prolong life. The genomic characterization of tumours can also give direction to the development of novel drugs. Next-generation tumour sequencing is increasingly becoming an essential part of clinical decision-making, and, as such, will require appropriate coordination for effective adoption and delivery. Recent findings: There are several challenges that will need to be addressed if we are to facilitate cancer genomics as part of routine community oncology practice. Recent research into this novel testing paradigm has demonstrated the barriers are at the individual level, while others are at the institution and societal levels. Summary: This article, based on the authors' experience in community oncology practice and summary of literature, describes these challenges so strategies can be developed to address these challenges to improve patient outcomes.